Pilomatrixoma in preauricular region. Case Report. - Oscar Venegas; Martín Nicola; Benjamín Martínez; Bárbara Olivos; Rodrigo Tovar (Universidad de Concepción., 2013)
Pilomatrixoma or calcifying epithelioma of Malherbe is a benign tumor derived from hair follicles. Frequently found in children and young adults. They are usually asymptomatic, solitary, firm or hard, freely mobile, dermal or subcutaneous nodules. We present a case of a girl with a pilomatrixoma in preauricular region.